Anti-JMH alloantibody in inherited JMH-negative patients leads to immunogenic destruction of JMH-positive RBCs. (13th June 2021) - Yuan, Zhaohu; Wei, Yaming; Chen, Xiaojie; He, Shufei; Cai, Kui; Zhong, Minglu; Huang, Huiying; Tong, Xinxin; Liu, Zhen; Yang, Xuexin
Summary: The clinical significance of the specific anti-John Milton Hagen (JMH) alloantibody in inherited JMH-negative patients remains unclear. During clinical blood transfusion, it is often classified as an anti-JMH autoantibody in acquired JMH-negative patients, which might further lead to the occurrence of haemolysis events. In this study, we found that the proportion of inherited JMH-negative people in the Guangzhou population was 0.41%, based on the study of 243 blood samples by flow cytometry. Gene sequencing analysis revealed two novel variants located in exon 11 (c.1348G>A, p.Ala449Thr) and exon 14 (c.1989G>T, p.Leu663Phe). Specific antigen presentation showed that JMH-positive RBCs (red blood cells) could be internalized by SEMA7A −/− dendritic cells (DCs) and that SEMA7A −/− DCs activated by the semaphorin 7a (Sema7a) protein or JMH-positive erythrocytes further induced activation of CD4 + T cells to secrete interferon (IFN)-γ. Transfusion of JMH-positive RBCs could lead to the production of the specific anti-JMH alloantibody in Sema7a knock-out (KO) C57 mice. After erythrocyte sensitization, complement C3 was specifically fixed, causing the destruction of JMH-positive erythrocytes. The anti-JMH alloantibody caused immunological destruction of JMH-positive erythrocytes and promoted the clearance of JMH-positive RBCs. We should be cautious when making conclusions about the clinical significance of the anti-JMH alloantibody. Graphical Abstract: